2005
DOI: 10.1037/0021-9010.90.4.659
|View full text |Cite
|
Sign up to set email alerts
|

From Ideal to Real: A Longitudinal Study of the Role of Implicit Leadership Theories on Leader-Member Exchanges and Employee Outcomes.

Abstract: The results of the present longitudinal study demonstrate the importance of implicit leadership theories (ILTs) for the quality of leader-member exchanges (LMX) and employees' organizational commitment, job satisfaction, and well-being. Results based on a sample of 439 employees who completed the study questionnaires at 2 time points showed that the closer employees perceived their actual manager's profile to be to the ILTs they endorsed, the better the quality of LMX. Results also indicated that the implicit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
486
3
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 536 publications
(541 citation statements)
references
References 80 publications
23
486
3
14
Order By: Relevance
“…The theory also asserts that leadership categorization has important ramifications for leader endorsement and leader influence, and ultimately leader effectiveness. Consistent with this view, Epitropaki and Martin (2005) found that highly prototypical leaders who matched followers' implicit leadership theories were more likely to forge better quality relationships with their followers, and have a positive influence on their followers' commitment and satisfaction at work.…”
Section: Leadership As a Social Cognitive Processmentioning
confidence: 72%
“…The theory also asserts that leadership categorization has important ramifications for leader endorsement and leader influence, and ultimately leader effectiveness. Consistent with this view, Epitropaki and Martin (2005) found that highly prototypical leaders who matched followers' implicit leadership theories were more likely to forge better quality relationships with their followers, and have a positive influence on their followers' commitment and satisfaction at work.…”
Section: Leadership As a Social Cognitive Processmentioning
confidence: 72%
“…However, disagreement arises as Epitropaki and Martin (2005) and Wu (2009) discussed that transactional leadership is more effective than transformational leadership style to achieve organizational goals and enhance employee commitment. Similarly, Marmaya et al (2011) also arguedthat the relationship between employee commitment and transactional leadership is more significant than transformational leadership style.…”
Section: Transformational Leadership Stylementioning
confidence: 99%
“…What's more, existing research also demonstrates positive relations between organizational commitment to the organization and indices of employee well-being [15]. Shimazu and Schaufeli [16] expect that job involvement predicts future well-being.…”
Section: Dialectical Relationshipmentioning
confidence: 99%